The Effect Of Emotional Intelligence Program On Leadership Skills Among Gifted Students In Saudi Arabia - Alzaidy, Adel Moneer A. (2021)
This study aimed to identify the effect of the emotional intelligence program on leadership skills among the gifted students in Saudi Arabia. This study intends to answer research questions that include the development, the effect of emotional intelligence program and viewpoints of gifted students regarding the effect of the emotional intelligence program on these skills.